Reading Comprehension Problem Faced by Indonesian Students at Secondary Schools - Indah Paramitha Indah; Sukardi Weda; Sahril (International Journal of Language, Education, and Literature, 2025)
This thesis aimed to find out problems are faced by students in comprehending descriptive text and the factors that cause students’ problems in comprehending descriptive text at SMPN 2 Galesong Utara. This research design used descriptive qualitative method. The subject of the research was students at Grade 7th in SMPN 2 Galesong Utara in academic year of 2023/2024. The sample are 30 students in class 7D and used purposive sampling to gain the data. The data were collected by reading test interview. The researcher found that There are 19.30% students who are difficulties in answering questions items for understanding vocabulary, there are 42.70% students who difficulties in are answering question items for understanding making inference and there are 14.48% students who difficulties in are answering question items to look for the detail information. that there were various difficulties encountered by the students in comprehending descriptive text, namely (1) understanding long sentence in the text, (2) inadequate instruction presented by teacher, (3) understanding vocabulary, and (3) house and school environment. In conclusion, there are 3 factors causing students in comprehending descriptive text at SMPN 2 Galesong Utara..